2019
DOI: 10.1242/jeb.212464
|View full text |Cite
|
Sign up to set email alerts
|

Thrust generation during steady swimming and acceleration from rest in anguilliform swimmers

Abstract: Escape swimming is a crucial behavior by which undulatory swimmers evade potential threats. The hydrodynamics of escape swimming have not been well studied, particularly for anguilliform swimmers, such as the sea lamprey Petromyzon marinus. For this study, we compared the kinematics and hydrodynamics of larval sea lampreys with those of lampreys accelerating from rest during escape swimming. We used experimentally derived velocity fields to calculate pressure fields and distributions of thrust and drag along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 48 publications
2
28
3
Order By: Relevance
“…In another study, incorporating 51 anguilliform and carangiform swimming fish species, it was shown that undulating fishes show increased tail beat amplitudes during linear accelerations compared to steady swimming [5]. This finding was corroborated by detailed analyses of bluegill sunfish showing increased head and tail amplitudes [7] and lamprey showing higher amplitudes along the entire body [6] during linear acceleration. Wise et al [7] also found indications of larger force production rather than the reorientation of axial forces during acceleration compared to steady swimming patterns, which differs slightly from the conclusions of [5] who documented vortex wake reorientation during acceleration.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…In another study, incorporating 51 anguilliform and carangiform swimming fish species, it was shown that undulating fishes show increased tail beat amplitudes during linear accelerations compared to steady swimming [5]. This finding was corroborated by detailed analyses of bluegill sunfish showing increased head and tail amplitudes [7] and lamprey showing higher amplitudes along the entire body [6] during linear acceleration. Wise et al [7] also found indications of larger force production rather than the reorientation of axial forces during acceleration compared to steady swimming patterns, which differs slightly from the conclusions of [5] who documented vortex wake reorientation during acceleration.…”
Section: Introductionmentioning
confidence: 80%
“…Coordinated body and tail movements linearly accelerate the fish forward rapidly. Nearly all previous analyses of linear fish acceleration consider accelerations while transitioning between steady swimming speeds and accelerations from rest have rarely been studied [6]. Fish typically alter their tail beat frequency and amplitude to accelerate between different steady swimming speeds, generating a vortex wake with geometry and orientation that differ from those of steady swimming [1,5,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To compare the kinematics and swimming of the lamprey, each animal was video recorded during steady state swimming according to Gemmell et al (2016) and (Du Clos et al, 2019)Du Clos et al (2020). Accordingly, lampreys were placed at one end of long (1.5 meter) tanks where swimming was initiated by touching the individual gently at the tail.…”
Section: Methodsmentioning
confidence: 99%